Record of Late Miocene glacial deposits on Isla Marambio (Seymour Island), Antarctic Peninsula - Marenssi, Sergio Alfredo (2009)
We report and describe two new small diamictite outcrops on Isla Marambio (Seymour Island), Antarctic Peninsula. These rocks rest on an erosional unconformity on top of the Eocene La Meseta Formation and are unconformably covered by glaciomarine rocks of the -Pliocene–Pleistocene Weddell Sea Formation. The lithology, fossil content and isotopic ages obtained strongly suggest that the rocks belong to the Hobbs Glacier Formation and support a Late Miocene age for this unit. Additionally, the dated basalt clast provides the oldest age (12.4 Ma) for the James Ross Island Volcanic Group recorded up to now. The here described diamictite cannot be confidently correlated with a glaciomarine unit previously assigned to the Late Eocene–Lower Oligocene taken as proof that initial expansion of ice on Antarctica encompassed the entire continent synchronously in the earliest Oligocene. However, it is now evident that there are likely to be more, short but important, stratigraphic sequences of key regional and Antarctic wide interest preserved on the plateau of Isla Marambio.